Troncos fósseis, tetrápodes triássicos, mesetas e gravuras rupestres: a percepção do geopatrimônio de São Pedro do Sul, Mata e São Vicente do Sul - Souza, Luiz Paulo Martins e (2023)
Geoconservation has become an innovative strategy for nature conservation, which, in addition to focusing on geodiversity, seeks to bond with local communities that are related to the abiotic and biotic elements of the space where they live. In addition to proposing “untouched sanctuaries of nature”, which must be far from human coexistence, geoconservation initiatives seek to integrate societies in nature conservation processes. Based on sustainable use, geodiversity becomes the basis for a local development strategy based on community-based tourism (geotourism), research, education, training, expansion and differentiation of local enterprises, in addition to strengthening traditional communities and women's empowerment. In this way, investigating the perceptions of local communities about the elements of geodiversity that are likely to compose a geoconservation strategy becomes a fundamental step, since, ultimately, those who really conserve the elements of nature are these communities, which in their day-to-day lives, live with such elements. In this context, the general objective of the present research was to understand how different segments of the population of São Pedro do Sul, Mata and São Vicente do Sul, perceive in terms of (1) degree of relevance, (2) possibility of income generation and (3) need for public or private policies for the conservation of geodiversity elements, related to fossil content, to the residual hills and to the archaeological records present in the territories of these municipalities. From a methodological approach that used a test with photographs and a semi-structured questionnaire, the research recognized that the fossil trunks that are in public squares, the fossils of Triassic tetrapods present in municipal museums, the Itaquatiá, Loreto and Seio de Moça hills, as well as the rock engravings of the Pedra Grande Archaeological Site, have a high degree of relevance for the local communities. On the other hand, the outcrops (Chiniquá outcrop) and all the fossil trunks that are in situ, are not so relevant for the interviewed populations. Also noteworthy is the significant difference in the perception and evaluation of these geodiversity materials between the younger population (school community) and the rest of the interviewed segments (entrepreneurs, general public and public administrators). The investigation also recognized the broad support of the respondents for the development of informative-interpretative materials on the evaluated geodiversity elements, as well as the recognition of the potential of these materials to leverage a local development strategy.